Science learning package using guided inquiry to increase students science process skills - R Riasha; M Nur; M T Hidayat (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The aim of this research is to produce a science learning package using guided inquiry model that validity, practicality, and effectiveness to increase students science process skills. This research was research design using three stages which are defining, designing, and developing from Four D- models. Learning package tested on 9st of Kamal 4 Junior High School. The research data obtained through the validation method, observation, test, and questionnaire. The result of the research showed that (a) the category of learning package developed is very valid, (b) learning activity is very successfully, (c) cognitive product achievement of student has increased in high category and cognitive process achievement of student has increased in high category, (d) students responded very positively to respond learning that is already implemented. The conclusion of this research are the science learning package using guided inquiry model were validity, practicality, and effectiveness used to increase students science process skills. The impacts of the research suggest that guided inquiry may stimulate the students science process skills